57 The Saga of Just One QTL; From Laying Hen Bone Strength to One Carbon Metabolism. (8th October 2021) - Dunn, Ian C; McCormack, Heather; de Koning, Dirk-Jan; Navarro, Alejandro Rodríguez; Schmutz, Matthias; Andersson, Björn; Cavero, David; Fleming, Robert; Wilson, Peter; Maidin, Maisarah
Abstract: Skeletal damage is a challenge for laying hens, as the adaptations for egg laying make them susceptible to osteoporosis. We know that activity, growth and puberty influence skeletal quality genetics. However, in this story, we follow the process of resolving a QTL for skeletal quality to a single gene. Providing both a nutritional and a genetic solution and illustrating another level of complexity. Using divergently selected populations in an F2 cross, a QTL for skeletal quality was described. Utilising a series of experiments in the commercial founder line the QTL was fine mapped on chromosome 1 and the differences in physiology of hens that segregated for markers at the locus defined e.g. tibia breaking strength 200.4 vs 218.1 Newton (p< 0.002). Transcriptome profiling of tibia from the high and low bone strength genotype revealed a highly differentially expressed gene co localising to the QTL, the enzyme cystathionine beta synthase (CBS). CBS is a component of one carbon metabolism. Plasma homocysteine, the substrate of CBS had a higher concentration in the genotype associated with poor bone quality. Homocysteine interferes with crosslinking of the collagen matrix, critical to bone formation. Homocysteine can be re-methylated into methionine, a limiting amino acid in laying hens, using betaine as a methyl donor. Testing the hypothesis that reducing plasma homocysteine by feeding betaine, a widely available feed additive, would improve bone quality in laying hens proved successful.This is just one component of a complex trait and its elucidation took us along unexpected routes. However, I am optimistic that with modern tools and an open mind we can progress more quickly. Alongside understanding the factors that determine skeletal quality genetics, the discovery of the mechanisms behind complex traits, although rarely easy, offer the potential for novel interventions to improve animal health and production.